Palmar fasciitis and polyarthritis, a rare paraneoplastic syndrome related to ovarian cancer. (27th February 2017) - van Marcke, C.; Seront, E.; Docquier, C.; Filleul, B.
Summary: Palmar fasciitis and polyarthritis syndrome (PFPAS) is an uncommon disorder characterized by diffuse inflammation of the palmar fascia, tendon sheaths, and joints of the fingers and wrists, which rapidly progresses to flexion contracture of the hands. This paraneoplastic syndrome, originally linked to ovarian carcinoma, has also been associated with multiple different malignancies. As PFPAS usually precedes the detection of cancer, its symptoms should raise the suspicion of an underlying malignancy and should be thoroughly investigated.